Self-determination in a work organization. - Deci, Edward L.; Connell, James P.; Ryan, Richard M. (Journal of Applied Psychology, 1989)
Research testing self-determination theory was discussed in terms of recent work on intrinsic moti-vation, participative management, and leadership. On three occasions, managers ' interpersonal ori-entations—toward supporting subordinates ' self-determination versus controlling their behavior— were related to perceptions, affects, and satisfactions of the subordinates. Data from 23 managers and their subordinates in a major corporation showed that managers ' orientations did correlate with the subordinate variables, although the magnitude of the relation varied, seemingly as a function of factors in the corporate climate. An organizational development intervention, focused on the concept of supporting subordinates ' self-determination, was provided for the managers. Evaluation of the program showed a clearly positive impact on managers ' orientations, though a less conclusive radia-tion to subordinates. To be self-determining means to experience a sense of choice in initiating and regulating one's own actions. Recent research linking self-determination to, enhanced creativity (Amabile, 1983), conceptual learning (Benware & Deci, 1984), self-es-teem (Deci, Schwartz, Sheinman, & Ryan, 1981), and general